EVALUASI PENURUNAN TINGKAT KEHILANGAN AIR KOTA LIMBOTO PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) KABUPATEN GORONTALO - Hunta, Syafrudin; Tome, Nurhediyati (Jurnal Teknik Sipil, Arsitek, Perencanaan Wilayah (J-TSIAP), 2023)
The aim of this research is to determine the estimated magnitude of the increase in clean water demand and the service level of the Limboto Unit PDAM until 2020, as well as to evaluate the distribution of water loss levels in the Limboto City SPAM clean water network. The research method used is a case study by analyzing and evaluating the required data, including data on the number of residents, number of customers and data on the production and distribution of PDAM Limboto Unit water for the last 5 years. This research is divided into several activity stages, namely: projection of the number of consumers and amount of clean water usage, analysis of needs and level of clean water services until 2020 and evaluation of the distribution of water loss levels in PDAM Limboto City. The research results show that PDAM's water distribution capacity in 2020 to serve customer needs according to the estimated population is 229.55 lt/s out of a total number of consumers of 88,146 people. Service coverage in 2011 in Limboto City has reached 78.01%. The level of water loss that occurs in the Limboto City SPAM clean water supply system is estimated for the distribution network on average at 9.80% and for the transmission network on average at 25.94%. According to the results of the analysis and evaluation, activities are needed to increase the capacity of the transmission network and production system in stages of 40-80 liters/second, adding reservoirs, adding and replacing pipes and meters in line with the increasing number of customers and the need for clean water until 2020.